Analisis Komparatif Biaya Klaim Pasien Diabetes Melitus Berdasarkan Tingkat Keparahan: Studi Big Data Jaminan Kesehatan Nasional - Zulkifli Walangadi; Siti Qomaria Usu; Marhawati Marhawati; Cici Nila Ardila; Luthfiana Nur (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2026)
Diabetes Mellitus (DM) poses a substantial financial burden on Indonesia’s National Health Insurance (JKN), particularly for inpatient services at Advanced Referral Health Facilities (FKRTL). The INA-CBGs payment system classifies cases by severity level to determine BPJS Kesehatan reimbursement. This study aimed to examine differences in BPJS Kesehatan claim costs according to DM severity levels among hospitalized patients. A quantitative comparative design was applied using the 2025 BPJS Kesehatan Sample Data. A total of 58,101 inpatient DM claims were analyzed using total sampling. The independent variable was INA-CBGs severity level, and the dependent variable was total BPJS Kesehatan claim cost. Data were analyzed descriptively and inferentially using the Kruskal–Wallis test followed by post-hoc Mann–Whitney U tests with Bonferroni correction. The results indicated a consistent increase in length of stay and median claim costs with higher severity levels. Median claim costs were IDR 4,038,200 for mild cases, IDR 5,748,650 for moderate cases, and IDR 8,627,650 for severe cases. Differences in claim costs across severity levels were statistically significant (p < 0.05). In conclusion, DM severity level is significantly associated with BPJS Kesehatan claim costs, indicating that the INA-CBGs system adequately differentiates reimbursement based on case complexity.